Asosiasi Adversity Quotient dengan Hasil Belajar Matematika Peserta Didik Jenjang SMP - Nurul Huda; Damar Damar (Pendidikan Matematika STKIP Kusuma Negara, 2021)
The purpose of this study was to determine whether there is a relationship between the students' adversity questions and the mathematics learning outcomes. This type of research is a quantitative research with correlational techniques. The research sample that was selected randomly to 50 students. The instrument to measure the adversity quotient variable used a questionnaire with a Likert scale and the variable instrument of mathematics learning outcomes used a multiple-choice form test, that had been tested for validity and reliability. The requirements test performed showed normal analysis results (Lilliefors test) and homogeneous (Fisher's test). The regression linearity test results of the regression line equation ?=1,947+0,795X. The test results used product trials when the r=0,605 was obtained. Reinforced the degree of significance with the test obtained the tvalue=5,267>2,01=ttable. This research conclusion that there is a significant positive relationship between adversity quotient and mathematics learning outcomes of seventh grade students at SMP Negeri 4 Cikarang Selatan with a contribution of 36,6%.